Going cold turkey!: An autoethnographic exploration of digital disengagement - Ghita Cristina; Thorén Claes (Nordicom Review)
As the dust of society-wide digitalisation settles, the search for meaningful technological encounters is becoming more urgent. While the Nordic countries embrace digitalisation, recent concerns regarding technology overuse have been gaining increased attention. This tendency is exemplified in practices of limiting digital use, called digital disengagement – an apparent paradox in Nordic societies where digital is the dominant paradigm. In this article, we explore the emergence of disconnection-centred devices called “dumbphones”, which cater to individuals wishing to escape hyperconnected lifestyles. Drawing on a new materialist perspective, we present a content analysis of dumbphones’ advertising material, followed by a collaborative autoethnographic study in which we replace our smartphones with dumbphones. We critically weigh the promises of the dumbphones against the actual experience of digital disengagement in Sweden. Our findings illustrate a struggle with digital technologies, even despite their absence, due to emerging workarounds and societal expectations of use.